Luminescent properties of Ag(i)/Cu(i) coordination polymers: crystal structures and high intensity luminescence of a PMMA-doped hybrid material based on a quinoline-2, 3-dicarboxylic acid ligand. Issue 22 (9th February 2015) - Song, Yang; Fan, Rui-Qing; Zhang, Hui-Jie; Liu, Zhi-Wei; Wang, Xue-Tao; Tan, Cai-Tu; Yang, Yu-Lin; Wang, Yu-Lei
Abstract : Preparation, characterization, crystal structure and different luminescent properties of Ag(i )/Cu(i ) coordination polymers: stable blue emission, thermochromism and PMMA-doped hybrid material. Abstract : Three one-dimensional (1D) Ag(i )/Cu(i ) coordination polymers, formulated as [Ag(2, 3-Hqldc)] n (Ag1 ), [Ag(3-qlc)]2 n (Ag2 ) and [CuI(3-Hqlc)] n (Cu1 ) based on the ligand quinoline-2, 3-dicarboxylic acid (H2 qldc), were synthesized through hydrothermal (solvothermal) method and structurally characterized by single-crystal X-ray diffraction, IR spectroscopy and elemental analysis. Molecular structural analysis reveals thatAg1 was a 1D + 1D → 1D infinite chain synthesized at a relatively low temperature 80 °C, which further forms a three-dimensional (3D) structure by π–π stacking interactions.Ag2 forms a 1D dimer chain structure and via π⋯π packing interactions shows a two-dimensional (2D) supramolecular network. BothAg1 andAg2 display stable blue luminescent in the solid state and in organic solvents (DMSO, CH3 CN and CH3 OH) at 298 K and 77 K. However, Cu1 possess a 1D ladder chain structure, which further forms a 2D structure by hydrogen bonding interactions.Cu1 shows tunable luminescence at 298 K and 77 K in the solid state with a large red-shift of 70 nm and the CIE color shifts from bright yellow (0.51, 0.48) to red (0.67, 0.30), indicating thermochromic luminescence forCu1 . After doping with poly(methylmethacrylate) (PMMA), not only are the luminescence intensity and lifetimes enhanced, but the thermal stability is also increased in comparison withCu1 . AfterCu1 was doped with PMMA (Cu1 @PMMA), the lifetime of the polymer film materialCu1 @PMMA increases and reaches a maximum at 1.0% ( τ = 95.57 μs), which is more than eight times longer than that ofCu1 ( τ = 13.78 μs).Cu1 @PMMA is confirmed as a bright yellow luminescent polymer film material.